Molecular Characterization and Functional Analysis of Two Petunia PhEILs - Liu, Feng; Hu, Li; Cai, Yuanping; Lin, Hong; Liu, Juanxu; Yu, Yixun (Frontiers in Plant Science, 2016)
Ethylene plays an important role in flower senescence of many plants. Arabidopsis ETHYLENE INSENSITIVE3 (EIN3) and its homolog EIL1 are the downstream component of ethylene signaling transduction. However, the function of EILs during flower senescence remains unknown. Here, a petunia EIL gene, PhEIL2, was isolated. Phylogenetic tree showed that PhEIL1, whose coding gene is previously isolated, and PhEIL2 are the homologs of Arabidopsis AtEIL3 and AtEIL1, respectively. The expression of both PhEIL1 and PhEIL2 is the highest in corollas and increased during corolla senescence. Ethylene treatment increased the mRNA level of PhEIL1 but reduced that of PhEIL2. VIGS-mediated both PhEIL1 and PhEIL2 silencing delayed flower senescence, and significantly reduced ethylene production and the expression of PhERF3 and PhCP2, two senescence-associated genes in petunia flowers. The PhEIL2 protein activating transcription domain is identified in the 353-612-amino acids at C-terminal of PhEIL2 and yeast two-hybrid and BiFC assays show that PhEIL2 interacts with PhEIL1, suggesting that PhEIL1 and PhEIL2 might form heterodimers to recognize their targets. These molecular characterizations of PhEIL1 and PhEIL2 in petunia are different with those of in Vigna radiata and Arabidopsis.